Bioenergetic dysfunction in Huntington's disease human cybrids - Ferreira, IL (2011)
In this work we studied the mitochondrial-associated metabolic pathways in Huntington's disease (HD) versus control (CTR) cybrids, a cell model in which the contribution of mitochondrial defects from patients is isolated. HD cybrids exhibited an interesting increase in ATP levels, when compared to CTR cybrids. Concomitantly, we observed increased glycolytic rate in HD cybrids, as revealed by increased lactate/pyruvate ratio, which was reverted after inhibition of glycolysis. A decrease in glucose-6-phosphate dehydrogenase activity in HD cybrids further indicated decreased rate of the pentose-phosphate pathway. ATP levels of HD cybrids were significantly decreased under glycolysis inhibition, which was accompanied by a decrease in phosphocreatine. Nevertheless, pyruvate supplementation could not recover HD cybrids' ATP or phosphocreatine levels, suggesting a dysfunction in mitochondrial use of that substrate. Oligomycin also caused a decrease in ATP levels, suggesting a partial support of ATP generation by the mitochondria. Nevertheless, mitochondrial NADH/NAD(t) levels were decreased in HD cybrids, which was correlated with a decrease in pyruvate dehydrogenase activity and protein expression, suggesting decreased tricarboxylic acid cycle (TCA) input from glycolysis. Interestingly, the activity of alpha-ketoglutarate dehydrogenase, a critical enzyme complex that links the TCA to amino acid synthesis and degradation, was increased in HD cybrids. In accordance, mitochondrial levels of glutamate were increased and alanine was decreased, whereas aspartate and glutamine levels were unchanged in HD cybrids. Conversely, malate dehydrogenase activity from total cell extracts was unchanged in HD cybrids. Our results suggest that inherent dysfunction of mitochondria from HD patients affects cellular bioenergetics in an otherwise functional nuclear background.